Decadal acidification in Atlantic and Mediterranean water masses exchanging at the Strait of Gibraltar - Flecha, Susana; Pérez, Fiz F.; Murata, Akihiko; Makaoui, Ahmed; Huertas, I. Emma (Springer Nature, 2019)
11 pages, 2 tables, 3 figures.-- This article is licensed under a Creative Commons Attribution 4.0 International License Seawater pH is undergoing a decreasing trend due to the absorption of atmospheric CO2, a phenomenon known as ocean acidification (OA). Biogeochemical processes occurring naturally in the ocean also change pH and hence, for an accurate assessment of OA, the contribution of the natural component to the total pH variation must be quantified. In this work, we used 11 years (2005–2015) of biogeochemical measurements collected at the Strait of Gibraltar to estimate decadal trends of pH in two major Mediterranean water masses, the Western Mediterranean Deep Water (WMDW) and the Levantine Intermediate Water (LIW) and assess the magnitude of natural and anthropogenic components on the total pH change. The assessment was also performed in the North Atlantic Central Water (NACW) feeding the Mediterranean Sea. Our analysis revealed a significant human impact on all water masses in terms of accumulation of anthropogenic CO2. However, the decadal pH decline found in the WMDW and the NACW was markedly affected by natural processes, which accounted for by nearly 60% and 40% of the total pH decrease, respectively. The LIW did not exhibit a significant pH temporal trend although data indicated natural and anthropogenic perturbations on its biogeochemical signatures Funding for this work was provided by the European Commission through the projects CARBOOCEAN (FP6-511176), CARBOCHANGE (FP7-264879), PERSEUS (FP7-287600) and COMFORT (H2020-820989) and by the Spanish Ministry of Economy and Competitiveness (CTM2006-28141-E/MAR, CTM2016-75487-R). S.F acknowledges the financial support of Canon Foundation in Europe Research Fellowships Program Peer reviewed